Outcomes of Cyclosporine A Treatment in Children with Steroid Resistant Nephrotic Syndrome at Vietnam National Children’s Hospital - Dem, Pham Van; Huong, Nguyen Thu; Lien, Nguyen Thi Thuy; Kien, Nguyen Thi; Nam, Thai Thien; Huonh, Nguyen Thi Quynh (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2018)
This paper describes the clinical, paraclinical features and the outcomes of cyclosporine A treatment in children with steroid resistant nephrotic syndrome. Subjects and methods : Descriptive prospective study enrolled 75 children with steroid resistant primary nephrotic syndrome, hospitalized at the Department of Nephrology-Dialysis, the Hospital of Paediatrics from January 2015 to December 2015. Results : 61.3% of the patients showed early resistance and 38.7% of the patients with late resistance. The most common clinical symptoms were edema - 100%, chronic renal failure - 12.0%, hematuria - 10.6%, and hypertension - 9.3%. A renal biopsy for 34 patients showed that 70.6% of these were with focal and segmental glomerulosclerosis (FSGS), 26.5% with minimal change disease (MCD), and 4.9% with diffuse fibrosis. After a 6-month cyclosporine A treatment, the proportion of response was 81.3%, of which, 69.3% showed complete remission and 12.0% with partial remission; but after 12 months, the given percentages gradually decreased. There were 8 end-stage renal disease patients (10.7%) died. Conclusion : Steroid resistant nephrotic syndrome in the children expressed very severe clinical symptoms and the mortality rate was high. Keywords Steroid resistant nephrotic syndrome, end-stage renal disease References [1] Banh T.H., Hussain-Shamsy N., Patel V. et al (2016), Ethnic Diffifences in Incidence and Outcomes of Chilhood Nephrotic Syndrome, Clinical Journal of the American Society of Nephrology, 11(10), (2016), 1760-1767. [2] Lê Nam Trà và Nguyễn Ngọc Sáng, Hội chứng thận hư kháng thuốc steroid, Sách giáo khoa Nhi khoa, Nhà xuất bản Y học, Hà Nội,(2013), 1150-1160. [3] Niaudet P, Steroid-resistant idiopathic nephrotic syndrome in children. www.uptodate.com, (2016), 01-15. [4] KDIGO: Clinical Practice Guideline for Glomerulonephritis, Steroid-resistant nephrotic syndrome in children. Kidney International Supplements 2, chapter 4, (2012), 172–176. [5] Schwartz George J., Alvaro Muñoz, Schneider Michael F. et al, New Equations to Estimate GFR in Children with CKD. Journal of the American Society of Nephrology, 20(3), (2009), 629–637. [6] Roy R., Mamun A., Haque S.S. et al, Steroid resistant nephrotic syndrome in children: Clinical presentation, renal histology, complications, treatment and outcome at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. International Organization of Scientific Research Journal of Pharmacy, 4 (11), (2014), 01-07. [7] Trần Hữu Minh Quân, Huỳnh Thoại Loan, Nguyễn Ðức Quang và cộng sự, Đặc điểm hội chứng thận hư kháng steroid tại bệnh viện Nhi Đồng I, Hội nghị Nhi Khoa năm 2014 tại bệnh viện Nhi đồng I, (2014), 2-6. [8] Đoàn Thị Thắm, Nhận xét kết quả điều trị hội chứng thận hư tiên phát kháng corticosteroid tại khoa Thận - tiết niệu bệnh viện Nhi Trung ương, Luận văn Thạc sĩ Y học, Trường Đại Học Y Hà Nội (2011). [9] Alberto Z., Oliveira A.L., Montalvão J.A. et al, Steroid-resistant idiopathic nephrotic syndrome in children: long-term follow-up and risk factors for end-stage renal disease, J. Bras. Nefrol, 35 (3), (2013), 191-199. [10] Mortazavi F. and Khiavi Y.S, Steroid response pattern and outcome of pediatric idiopathic nephrotic syndrome: a single-center experience in northwest Iran, Therapeutics and Clinical Risk Management, 7, (2017), 167-171. [11] Özlü S.G., Demircin G., Tökmeci N. et al, Long-term prognosis of idiopathic nephrotic syndrome in children. Renal Failure, 37(4), (2015), 672-677.